1997
DOI: 10.1073/pnas.94.25.13786
|View full text |Cite
|
Sign up to set email alerts
|

Genetic recombination of poliovirus in a cell-free system

Abstract: Genetic recombination of plus-strand RNA viruses is an important process for promoting genetic variation. By using genetically marked poliovirus RNAs, we have demonstrated that genetic recombination can occur in a cell-free system that generates infective virus from added poliovirus RNA. Recombinant polioviruses were isolated, and the region of crossing over was roughly mapped. Recombinants could be isolated even under conditions where the yield of viruses from one of the parental RNAs was depressed to levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 26 publications
2
52
0
2
Order By: Relevance
“…However, the frequency of such recombination events is predicted to be far below detection within the timeframe and reporter expression levels of our system. By analogy with other positivestranded RNA viruses, intertypic recombination rates, e.g., between the type 1 replicon and the type 2 helper BVDV, are predicted to occur with a frequency of ϳ10 Ϫ8 (12,17,43,57). Thus, RNA recombination seems unlikely as the mechanism yielding the luciferase expression observed in our studies.…”
Section: Discussionmentioning
confidence: 60%
“…However, the frequency of such recombination events is predicted to be far below detection within the timeframe and reporter expression levels of our system. By analogy with other positivestranded RNA viruses, intertypic recombination rates, e.g., between the type 1 replicon and the type 2 helper BVDV, are predicted to occur with a frequency of ϳ10 Ϫ8 (12,17,43,57). Thus, RNA recombination seems unlikely as the mechanism yielding the luciferase expression observed in our studies.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, characterization of the recombination sites within the poliovirus genome at nonphysiological and physiological conditions revealed that severe restrictions were applied to recombination within the P1 region at physiological conditions. Using an in vitro system for studying recombination in the poliovirus genome, Duggal et al (1997) observed fewer limitations of recombination between poliovirus genomes in vitro than in vivo. This suggests that recombination may occur outside eventual hot spots of recombination.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the genetic lineage represented by the prototype strain of echovirus 9 (EV9H) is, as expected, closely related to the Barty genotype of EV9 (EV9B) in the structural genes while the non-structural genes of the P3 region are closely related to a lineage represented by the echovirus 18 prototype (EV18M) (Andersson et al, 2002). A recombination site was estimated by a maximum-likelihood approach to the 2C gene, one region that is a frequent recombination spot in polioviruses (Duggal et al, 1997;Duggal & Wimmer, 1999). However, the impact of recombination on the biology and evolution of enteroviruses has not been seriously assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to observe copy-choice recombination between poliovirus genomes in a cell-free system has been demonstrated recently by Kirkegaard (46) and Wimmer (47). Notwithstanding, these experiments utilized a HeLa cell extract, and all of the poliovirus proteins were present.…”
Section: Template Switching Is the Primary Pathway For Formation Of Pmentioning
confidence: 99%